Genetic and functional insights into CDA-I prevalence and pathogenesis. Issue 3 (9th June 2020) - Olijnik, Aude-Anais; Roy, Noémi B A; Scott, Caroline; Marsh, Joseph A; Brown, Jill; Lauschke, Karin; Ask, Katrine; Roberts, Nigel; Downes, Damien J; Brolih, Sanja; Johnson, Errin; Xella, Barbara; et al.
Abstract : Background: Congenital dyserythropoietic anaemia type I (CDA-I) is a hereditary anaemia caused by biallelic mutations in the widely expressed genes CDAN1 and C15orf41 . Little is understood about either protein and it is unclear in which cellular pathways they participate. Methods: Genetic analysis of a cohort of patients with CDA-I identifies novel pathogenic variants in both known causative genes. We analyse the mutation distribution and the predicted structural positioning of amino acids affected in Codanin-1, the protein encoded by CDAN1 . Using western blotting, immunoprecipitation and immunofluorescence, we determine the effect of particular mutations on both proteins and interrogate protein interaction, stability and subcellular localisation. Results: We identify six novel CDAN1 mutations and one novel mutation in C15orf41 and uncover evidence of further genetic heterogeneity in CDA-I. Additionally, population genetics suggests that CDA-I is more common than currently predicted. Mutations are enriched in six clusters in Codanin-1 and tend to affect buried residues. Many missense and in-frame mutations do not destabilise the entire protein. Rather C15orf41 relies on Codanin-1 for stability and both proteins, which are enriched in the nucleolus, interact to form an obligate complex in cells. Conclusion: Stability and interaction data suggest that C15orf41 may be the key determinant of CDA-I and offer insight into the mechanism underlying this disease. Both proteins share a common pathway likely to be present in a wide variety of cell types; however, nucleolar enrichment may provide a clue as to the erythroid specific nature of CDA-I. The surprisingly high predicted incidence of CDA-I suggests that better ascertainment would lead to improved patient care.